Pengaruh Gaya Kepemimpinan Konsultatif dan Tuntutan Tugas Terhadap Komitmen Organisasi pada PT. Bank Mandiri (Persero) Cabang Banda Aceh - Syamsul Rizal (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2018)
The purpose of this study was to determine the effect of consultative leadership style and task demands on organizational commitment of employees at PT. Bank Mandiri (Persero) Banda Aceh Branch and to find out how much influence leadership and the demands of the task of employee organizational commitment at PT. Bank Mandiri (Persero) Banda Aceh Branch. This research was conducted at PT. Bank Mandiri (Persero) Banda Aceh Branch. The object of this research is all employees at PT. Bank Mandiri (Persero) Banda Aceh Branch. This study will present how the influence of leadership and the demands of the task, on organizational commitment of employees at PT. Bank Mandiri (Persero) Banda Aceh Branch, with a total of 47 respondents. Based on the results of the F-test (simultaneous), it shows that all the variables studied have a significant effect on increasing the commitment of employees of PT. Bank Mandiri (Persero) Banda Aceh Branch with a value of Fcount> Ftable, at a significance level = 5%. Based on the results of the t-test (partially) the variables that have a significant effect on the commitment of the employees of PT. Bank Mandiri (Persero) Banda Aceh Branch is a task demand variable with a t-count value greater than the consultative leadership variable having a smaller t-count value.